Evaluation of dimensional stability, compressive resistance, and detail reproduction of thermoplastic resin (BDIMPRESS), elastomeric and composite bite registration material: An in vitro study - Sai Kiran Koppolu; P S Manoharan; E Rajkumar; G Ezhumalai (Wolters Kluwer Medknow Publications, 2023)
Aim: The fabrication of an accurate prosthesis depends mainly on precise recording of the maxillo-mandibular relationship of the patient and transferring it to the articulator. BDIMPRESS is a new thermoplastic material that has been proposed as a potential material to be used as an inter-occlusal registration, but there has been no literature evidence regarding its application as a bite registration. The main purpose of this study is to evaluate and compare the dimensional stability, detail reproduction, and compressive resistance of new interocclusal recording material with other two commonly used materials. Settings and Design: In Vitro Comparative study. Materials and Methods: The study was conducted according to ADA Specification standards of testing for dimensional stability, detail reproduction and compressive resistance. Specimens were prepared for three different materials (Thermoplastic resin, Polyvinyl siloxane, and Bis- acrylic) with 12 samples each. Statistical Analysis Used: One way ANOVA was done for statistical analysis. Results: Polyvinyl siloxane material was dimensionally stable (mean at 1 hr: 24.928 mm; 24 hrs: 24.919 mm & 48 hrs: 24.912 mm) followed by Bis- acrylic material (mean at 1 hr: 24.851 mm; 24 hrs: 24.825 mm & 48 hrs: 24.815 mm). On one way ANOVA, strong significance was observed between groups (P = 0.00). Thermoplastic resin showed higher amount of detail reproduction with 10 (out of 12 samples) samples showing satisfactory results. While bis- acrylic material showed the least compressive resistance (Strain %: 0.484%; Displacement- 0.0990mm). One-way ANOVA showed presence of significance between the groups (P = 0.024). Conclusion: Polyvinyl siloxane showed superior dimensional stability, thermoplastic resin showed better detail reproduction and bis- acrylic showed high resistance to compression over other materials.